Artificial water sediment regulation scheme influences morphology, hydrodynamics and nutrient behavior in the Yellow River estuary - Xu, Bochao; Yang, Disong; Burnett, William C.; Ran, Xiangbin; Yu, Zhigang; Gao, Maosheng; Diao, Shaobo; Jiang, Xueyan (Journal of hydrology (Amsterdam), 2016)
•A small delta was newly formed in the Yellow River estuary during a WSRS.•Material distribution altered to a two-plume pattern.•Estuarine mixing was two times stronger during WSRS.•Nutrients were mostly consumed within one to two weeks after entry to the estuary.•Terrestrial nutrient influenced area was 2–3 times larger during WSRS. Anthropogenic controls on water and sediment may play important roles in river system transformations and morphological evolution, which could further affect coastal hydrodynamics and nutrient behavior. We used geochemical tracers to evaluate the influence of an intentional large release of water and sediment during the so-called “Water Sediment Regulation Scheme” (WSRS) on estuarine morphology, hydrodynamics and nutrients in the Yellow River estuary, China. We discovered that there was a newly formed small delta in the river mouth after the 2013 WSRS. This new morphologic feature altered terrestrial material distribution patterns from a single plume to a two-plume pattern within the estuary. Our results show that the WSRS significantly influenced the study area in the following ways: (1) Radium and nutrient concentrations were significantly elevated (two to four times), especially along the two river outlets. (2) Estuarine mixing was about two times stronger during WSRS than before. Average aerial mixing rates before and during WSRS were 50±26km2d−1 and 89±51km2d−1, respectively. (3) Our data is consistent with P limitation and suggest that stoichiometrically based P limitation was even more severe during WSRS. (4) All river-derived nutrients were thoroughly consumed within one to two weeks after entry to near-shore waters. (5) The extent of the area influenced by terrestrial nutrients was two to three times greater during WSRS. Human influence, such as triggered by WSRS regulations, should thus be considered when studying biogeochemical processes and nutrient budgets in situations like the Yellow River estuary.